EXERCISE TRAINING IN PEOPLE WITH A STABILIZED CHRONIC RESPIRATORY DISEASE: A SCOPING REVIEW - Luis Gaspar; Dulce Ferreira; Francisco Vieira; Paulo Machado; Miguel Padilha (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Introduction: Pulmonary Rehabilitation is (PR) integrates the non-pharmacological component of the clinical guidelines for the control and treatment of chronic respiratory diseases. The Rehabilitation Nurse (RN), integrated into a multidisciplinary team, designs, implements and monitors PR programs that include exercise training. Being the nursing disciplinary knowledge one of the pillars of clinical decision and the guarantor of the quality and safety of nursing care becomes relevant to know the impact of these programs, conducted by RN, in order to improve clinical practice. Objective: To know the impact of RR programs, conducted by nurses, on people with chronic respiratory disease. Methodology: Scoping review with Joanna Briggs Institute® methodology using two independent reviewers. Results: We included 10 studies that showed that nurse-led PR programs increase exercise tolerance, quality of life, functional independence, and reduce dyspnea and anxiety. Conclusion: The PR performed by RN in patients with chronic respiratory disease is overlapping with the latest evidence.